Astrocytes and human artificial blood-brain barrier models - Tanja Zidarič; Lidija Gradišnik; Tomaž Velnar (Biomolecules & Biomedicine, 2022)
The blood-brain barrier (BBB) functions as a highly selective border of endothelial cells, protecting the central nervous system from potentially harmful substances by selectively controlling the entry of cells and molecules, including components of the immune system. To study the BBB properties, find suitable therapies, and identify new drug targets, there is a need to develop representative in vitro BBB models. In this article, we describe the astrocyte roles in the BBB functioning and human in vitro BBB models.